Quod vitae sectabor iter? Salamanca between city paths and humanity in the path - Lacca, Emanuele (Labyrinth, 2020)
This paper aims to analyze the façade and staircase of the historic building of the University of Salamanca as an expression of the relationship between philosophy, theology and art in the Spanish Siglo de Oro, and will try to provide a new perspective on the sculptural elements present in both spaces of the university. There are few interpretations on this subject, but they all converge on understanding sculptures as an expression of the myth of the Spanish monarchy. This essay, instead, will show how those same elements can be read in relation to the moral and anthropological needs of 16th century humanity and, thus, that the relationship between university spaces and the people who frequent them is even closer. To enter a space, according to such an interpretation, does not simply mean to use it, but to frequent it and understand in it and from it reflections for everyday life.